Internet public opinion on climate change: a world views analysis of online reader comments. Issue 1 (2014) - ,; ,; ,; ,
Abstract : Purpose – The purpose of the study was to assess the representation of different world views with respect to climate change in public opinion on the internet.Design/methodology/approach – The authors conducted this world views analysis by means of a content analysis of publicly expressed opinions in the form of online lay reader comments to articles on climate change, published on Dutch newspaper web sites between August 2002 and December 2009. The comments were assigned to the world views of two typologies commonly used in ex ante assessment of climate policies. The classification of an online reader comment was based on world view specific keywords and positions on climate change.Findings – From a set of 2, 148 comments to 168 articles found on the web sites of 19 newspapers, 314 comments could be assigned to a particular world view. For both typologies, the distribution of comments over the different world views was highly uneven, with world views characterized as "climate sceptic" scoring more than 90 per cent of the assigned comments. The strong dominance of these "climate sceptic" world views was independent of year, newspaper, and scope of the article.Practical implications – These findings are in stark contrast with the outcomes of public opinion surveys indicating that only a minority of the population has a preference for a "climate sceptic" world view. The most plausible explanation for this difference is that the contributors of online reader comments are not representative for the Dutch population at large. However, as internet‐based opinions have a proven potential to strongly influence the opinion of the general public and politicians on climate change, the authors advise analysts to pay due attention to "climate sceptic" world views in ex ante assessment of the societal support for climate policies.Originality/value – For a world views analysis, the study is unique both in its focus on internet public opinion and the data source used.